A case of plasmacytoma with widespread metastasis in a dog - Osman Dagar; Aysenur Tural; Zeynep Celik; Fatih Mehmet Ozturk; Mehmet Tuzcu; Erhan Gulcicek (Eurasian Journal of Veterinary Sciences)
In this study, a case of plasmacytoma with widespread metastasis in a nine-year-old male Rottweiler dog was described by histopathological and immunohistochemical methods. Macroscopic examination revealed multifocal white or pink-red colored masses ranging in size from 0,5 to 3 cm in the lung, liver, mediastinal and mesenterial lymph nodes, spleen, heart, pancreas, intestine and kidneys. In microscopic examination, tumor foci consisting mostly of atypical plasma cells were observed in the lung, liver, spleen, pancreas, mediastinal and mesenteric lymph nodes, intestine, and kidneys. Tumor-type giant cells were observed in tumor foci in the lung, mitotic figures in tumor foci in other organs, including the lung, and abundant tumor cells in capillary vessels. In Methyl Green Pyronin staining of lung, liver, spleen, pancreas, mediastinal and mesenterial lymph nodes, intestine and kidney sections, the cytoplasm of plasma cells was observed to be stained pink. Congo Red staining applied to liver and spleen sections showed amyloid deposits stained in brick red color. In addition, in the immunohistochemical staining of lung, liver, spleen, pancreas, mediastinal and mesenterial lymph nodes, intestine and kidney sections with Proliferating Cell Nuclear Antigen (PCNA) antibody, severe immunoreactivity was detected in tumor cells. As a result, due to the presence of rarely reported widespread metastases in the lung, liver, spleen, pancreas, mediastinal and mesenterial lymph nodes, intestine and kidneys of the diagnosed plasmacytoma case, it was deemed appropriate to publish the case in order to contribute to the literature by attracting the attention of veterinarians.